Pembuatan Bank Sampah Menggunakan Atap Baja Ringan Rangka Waren dengan Material Penyusun Bangunan Limbah Beton di Dusun Kejoyo, Desa Tambong, Kecamatan Kabat, Banyuwangi: Making a Waste Bank Using a Light Steel Roof Waren Frame with Concrete Waste Building Materials in Kejoyo Hamlet, Tambong Village, Kabat District, Banyuwangi - Hutasoit, Eva Olivia; Khomari, Mohamad Galuh; Rodiyani, Megalita; Kanom, Kanom (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Community Self-Help Group (KSM) Istana Sumber Suci, Tambong Village is a Village Revitalization Movement to help reduce waste through recycling plastic waste, which is overwhelmed because it has to collect waste from each household in Tambong Village. Meanwhile, the plastic waste that is collected has not been sorted and is even mixed with other organic materials. This encourages the provision of a Waste Bank (TPS) using a lightweight steel roof to provide facilities in the form of waste sorting infrastructure that can be used by KSM to manage waste. The manufacture of lightweight steel roofs is a novelty because the material is developing and becoming a material that realizes sustainable construction. The main structure in making a waste bank is lightweight steel with a C-channel profile installed according to the Warren truss system, which is a very popular truss structure system and is easy to identify because its construction is in the form of an equilateral triangle. Warren truss has a structure made of equilateral triangles, famous for its ability to distribute the load evenly across different parts. The wall pair uses concrete waste as a material for making up the fill in the waste bank placement so that it can make the construction of the wall faster. The wall pair uses concrete waste divided based on 3 zonings (3R: reduce, recycle, reuse) given a partition to determine the type of waste categorized as plastic, metal, and paper, while organic waste can be used for fertilizer.